(untitled) (Research, Society and Development, 2020)
This study aimed to investigate the effects of psyllium (P) and water (W) on dough Mixolab® parameters, and their relationship with gluten-free bread (GFB) physical properties and acceptability. A 2² factorial design with three center points was used, in which P levels ranged from 2.86 to 17.14% and W levels from 82.14 to 117.86% on a flour basis. Samples were compared to a control GFB (0P:100W), and data were evaluated using regression models and multiple factor analysis (MFA). The predicted model equations were significant (R2adj= 82-99%, p<0.05) and showed that P increased dough consistency (C1), protein weakening (C2), gelatinization (C3), stability (C4) and retrogradation (C5) of starch, whereas W or its interaction with P decreased these parameters. MFA’s three dimensions explain 94.86% of the total variation. Factor 1 (57.02%) positively discriminates the loaf-specific volume and all acceptability attributes, but negatively discriminates crumb firmness and C1, C2, C3, C4, and C3-C4 Mixolab parameters, especially in the 2.86P:82.14W sample. Factor 2 (26.30%) positively discriminates the C5, C1-C2, and C5-C4 Mixolab parameters and central points of the study, but negatively discriminates the control GFB. Factor 3 (11.54%) positively discriminates crumb moisture and 2.86P:117.86W and 17.14P:117.86W samples, unlike 2.86P:82.14W, which is negatively discriminated. We found results regarding dough Mixolab parameters to explain P and W influence and its capability of predicting GFB physical properties and acceptability.